Pengaruh Konten Pemasaran dan Kualitas Produk di Media Sosial Instagram Erigo Terhadap Keputusan Pembelian Pelanggan - Muhammad Sulthan Rivansyah; Beny Witjaksono (Universitas 45 Surabaya, 2024)
In an increasingly developing era, the use of the internet in marketing in Indonesia is the right choice for business people, because all circles use the internet. One of the internet developments in terms of improving business is using social media. This requires companies to be able to compete with other companies in expanding and accelerating their marketing activities, one of which is through creating content that is put into social media. In their marketing activities, many companies use Instagram social media, one of which is Erigo, because Instagram is one of the phenomenal social media among the public. Instagram social media in Indonesia is ranked as the second most users in 2022 with 84.8% of users. This study aims to see whether there is an influence between marketing content and product quality on Instagram social media on customer purchasing decisions in DKI Jakarta. This research uses a quantitative analysis method approach. This study applied purposive sampling technique with a sample size of 90 respondents. Data processing in this study used the SPSS (Statistical Program For Social Science) version 27.0 program. The results of this study indicate that marketing content has a positive effect on purchasing decisions, product quality has a positive effect on purchasing decisions, and marketing content and product quality have a positive effect on purchasing decisions.